Mobile Wallets: Beyond Cash and Card, The Rise of Mobile Wallets alongside integration with CUPI and blockchain - Tanishka Chauhan; Sameep Shukla; Radhika Maheshwari; Shraddha Sharma; Dr. Swati Namdev (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
Mobile wallets have emerged as a pivotal tool in transforming consumer behavior and revolutionizing the way transactions are conducted. This research paper delves into the multifaceted impact of mobile wallets on merchant transactions, exploring their potential to drive cashless economies and enhance customer experiences. Through a comprehensive analysis of existing literature, case studies, and empirical data, this study examines the factors influencing mobile wallet adoption among merchants and consumers, the challenges and opportunities presented by this technology, and its potential to reshape the retail landscape. By shedding light on the intricate dynamics between mobile wallets and merchant transactions, this research aims to contribute to a deeper understanding of the evolving digital economy and inform future policy decisions and business strategies. Through a combination of literature review, empirical research, and case studies, this paper seeks to contribute to the ongoing discourse on mobile wallets and their role in shaping the future of commerce. To further enhance the scope of cashless and secure merchant transactions, this paper introduces CUPI (Crypto UPI), a blockchain-based innovation designed to replicate the speed and simplicity of UPI systems for cryptocurrency transactions. By leveraging Layer 2 blockchain solutions and advanced consensus mechanisms, CUPI bridges the gap between decentralized cryptocurrencies and real-time transaction requirements in commerce. The findings will be valuable to policymakers, technology providers, merchants, and consumers alike, offering insights into the opportunities and challenges associated with mobile wallet adoption. Furthermore, the research examines the potential implications of mobile wallets on various industries, including retail, hospitality, and transportation.